Findings of a Pilot Study Investigating the Effects of Mediterranean Diet and Aerobic Exercise on Cognition in Cognitively Healthy Older People Living Independently within Aged-Care Facilities: The Lifestyle Intervention in Independent Living Aged Care (LIILAC) Study. Issue 5 (18th April 2020) - Hardman, Roy J; Meyer, Denny; Kennedy, Greg; Macpherson, Helen; Scholey, Andrew B; Pipingas, Andrew
ABSTRACT: Background: Cognitive decline and Alzheimer disease are more prevalent in our aging population. Modifiable risk factors, such as diet and sedentary lifestyle, have been proposed as key to potentially ameliorating cognitive decline. Both exercise and Mediterranean diet (MedDiet) have been linked to reduced levels of cardiovascular disease and other comorbidities. Higher levels of exercise and MedDiet adherence may prove to be cognitively protective, both individually and synergistically. Objectives: The aim was to investigate the effect of a 6-mo program of MedDiet, exercise, and a combination of both, on cognition, mood, and general health in older persons living independently in aged-care communities. Methods: The Lifestyle Intervention in Independent Living Aged Care (LIILAC) Study (ACTRN12614001133628) involved 102 participants, aged 60–90 y, who were randomly assigned to 1 of 4 intervention groups. Change in overall memory performance was assessed as the primary outcome. Additionally, changes in cognitive task performance, as well as mood, wellness, cardiovascular function, and blood biomarkers, were investigated. Results: While there was no significant change in overall memory performance, there was a significant improvement in spatial working memory performance in the combined exercise and diet group, relative to controls. This combined intervention group also showed an overall improvement in their emotional state, as assessed by the Depression Anxiety Stress Scale, as did the exercise-only group. Conclusions: This research indicates that diet and exercise programs have the potential to improve aspects of cognition and mood in an aging population. However, given the lower than optimal sample size and lack of resources to reinforce the interventions during the trial, further larger randomized controlled trials are required to substantiate whether the introduction of diet and exercise programs into independent-living facilities is a viable method to preserve cognitive health in older people. This trial was registered at www.ANZCTR.org.au ACTRN 12614001133628 (LIILAC Study) Abstract : This pilot study investigated the effect of a six-month lifestyle intervention program of diet, exercise, and a combination of both, on cognition, mood, and general health in older persons living independently. This unique study was conducted in 15 independent living facilities with testing and administration of interventions to 102 participants aged 60–90 within their own living environments. Modifiable risk factors, such as diet and sedentary lifestyle, have been proposed as key to potentially ameliorating cognitive decline. Both exercise and Mediterranean diet (MedDiet) have been linked to reduced levels of cardiovascular disease and other comorbidities. Higher levels of exercise and MedDiet adherence may prove to be cognitively protective, both individually and synergistically. This research indicated that diet and exercise programs have the potential to improve aspects of cognition and mood in an aging population. This study has informed a larger study, currently underway, investigating effects of MedDiet and walking program on cognitive decline and general health in a similar demographic.